Assessment and Management of Postoperative Pain among Nurses at a Resource-Constraint Teaching Hospital in Ghana. (18th July 2019) - Mahama, Faisal; Ninnoni, Jerry P. K.
Abstract : Background. Postoperative pain remains one of the greatest concerns for patients following surgical procedures. Nurses play an essential role in postoperative pain assessment and management, especially within the first few days after surgery. Objective. The study investigated how nurses in a resource-constraint hospital in Ghana assessed and managed postoperative pain. Methods. This was an explorative qualitative study involving 12 registered nurses practising in the largest referral hospital in Ghana. Data was gathered using a semistructured interview guide. Demographic characteristics of participants were summarized using descriptive statistics. Data were analysed using Kvale's three phases for analysing qualitative data. First, the entire text was read again to identify meaning units which were then condensed. Second, the condensed texts were read again and interpreted. Finally, the condensed data containing similar meaning were coded and then sorted into subthemes. Results. It was found that some nurses have never used any pain assessment tool due to lack of standard tool for assessing postoperative pain. The majority of nurses reported that managing pain by using medication was the norm especially in the first 24 hours after surgery. Conclusion. Although participants may have some knowledge of assessing and managing postoperative pain, this knowledge was not largely used to manage postoperative pain effectively, partly because of resource constraints. Therefore, there is the need for adequate training and with provision of resources, it is imperative that the use of standardized pain assessment scales could help in the proper assessment and management of postoperative pain in this setting.